2020
DOI: 10.1016/j.techfore.2020.120054
|View full text |Cite
|
Sign up to set email alerts
|

Emerging green technologies for vehicle propulsion systems

Abstract: Breno Nunes 2 Geciane Porto 3 IntroductionThe climate change caused by greenhouse gases emissions in the atmosphere has been widely discussed for years. The transport area is one of the largest contributors for this scenario accounting for 23% of total CO2 emissions. This is because 95% of the energy used in transport comes from fossil fuels (Sims et al., 2014). Globally, transport is likely to continue being a big source of pollution, particularly urban air pollution. While the mobility by car is forecast to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 71 publications
(88 reference statements)
1
6
0
Order By: Relevance
“…More specifically, R&D collaboration does not affect the probability of a firm's decision to eco-innovate nor the correlation coefficient of the unobserved heterogeneity of the two equations is significant (see the lower part of Table 3). This result is in line with recent evidence documenting that organisations tend to be conservative in collaborating with external partners to protect their technologies and avoid imitation (de Paulo et al, 2020).…”
Section: The Decision To Develop Environmental Innovations In the Inn...supporting
confidence: 90%
“…More specifically, R&D collaboration does not affect the probability of a firm's decision to eco-innovate nor the correlation coefficient of the unobserved heterogeneity of the two equations is significant (see the lower part of Table 3). This result is in line with recent evidence documenting that organisations tend to be conservative in collaborating with external partners to protect their technologies and avoid imitation (de Paulo et al, 2020).…”
Section: The Decision To Develop Environmental Innovations In the Inn...supporting
confidence: 90%
“…China's rapid growth in developing green technologies is evident in several energy-related fields (De Paulo et al, 2020). This study contributes to how ESCOs in China are strategizing the development of their technological capabilities.…”
Section: Discussionmentioning
confidence: 95%
“…Subsequently, Verspagen (2007) proposed an evolution of the methodology by adopting the SPLC algorithm (Search path link count) in the analysis of patent networks and citations to identify better paths and point out the main routes for a technology. The confirmation about the accuracy of this method can be confirmed in publications on technological routes using ARS and SPLC in different knowledge domains (De Paulo & Porto, 2018;De Paulo et al, 2020;Picanço-Castro et al, 2020;Basso et al 2021).…”
Section: Knowledge Evolution Through Route Analysismentioning
confidence: 56%
“…The so-called emerging knowledge is represented by the most recent articles and portray theoretical or practical aspects about the main theme analyzed. Similar to the analysis of emerging and promising technologies through patents (Pereira et al, 2018a;De Paulo et al, 2020), the articles found herein at the top of the route refer to what is newest and most relevant on the subject of IoT and Smart Homes: new for being a more recent publication than the other articles of the route; and relevant for being a constituent part of a trajectory that interconnects the most referenced knowledge chain on IoT and Smart Homes. The intermediate level of knowledge, on its turn, represents scientific contributions that mediate basic research on the theme with more recent ones.…”
Section: Knowledge Route Of Iot and Smart Homesmentioning
confidence: 80%